Adoption of a novel smart mobile‐health application technology to track chronic immunosuppression adherence in solid organ transplantation: Results of a prospective, observational, multicentre, pilot study. Issue 5 (16th March 2021) - Melilli, Edoardo; Cestone, Giuseppe; Revuelta, Ignacio; Meneghini, Maria; Lladó, Laura; Montero, Nuria; Manonelles, Anna; Diaz, Maribel; Coloma, Ana; Torregrosa, Vicenç; Baliellas, Carme; Cruzado, Josep M.; et al.
Abstract: Background: Low adherence to chronic immunosuppression is associated with suboptimal transplantation outcomes. Mobile‐health technology is a promising tool to monitor medication adherence, but data on patient engagement to these tools are lacking. Methods: Prospective, observational, multicenter, 2‐phase trial in kidney and liver transplant recipients, investigating the degree of engagement to TrackYourMed ® (TYM), a novel m‐Health technology with a QR code‐scan app to track immunosuppression adherence and its association with drug monitoring. Results: Out of 204 consecutive transplant patients, 90 patients were eligible to participate. 61 (68%) used TYM regularly, 21 (23%) never or barely used it, 5 (5.5%) were irregular users, and 3 (3.3%) were lost to follow‐up. 6‐month total correct intakes (CIN) ranged between 69%–76%, 12%–19% intakes were out‐of‐time (OUT), and 9%–12% were missed (MIS). Notably, a rate of intakes out of the scheduled time higher than 20% in the 6 days prior to blood immunosuppressant trough levels was associated with a higher intra‐patient variability (17 IQR 13–21% vs. 29 IQR 23%–36%, p = .001), and with a higher dose‐adjustment ( p < .001). At 1 year, 53(59%) patients were still active users of TYM. Conclusions: Implementing m‐Health technologies promoting immunosuppression adherence may be useful for a relevant number of transplant patients and help transplant physicians identifying erratic immunosuppression adherence.